Role of muscoid flies in the ecology of shiga toxin-producing Escherichia coli (STEC) in confined cattle environments - Puri Giri, Rukmini (Kansas State University, 2015)
House flies (Musca domestica L.) and stable flies (Stomoxys calcitrans L.) are insects of medical and veterinary importance. House flies are recognized as mechanical vectors of human foodborne pathogens and stable files are known for their painful bites resulting in reduction of body weight gain and milk production in cattle. The larval development of both fly species takes place in decaying organic materials (primarily animal manure), resulting in large fly populations in confined cattle environments. Shiga toxin-producing Escherichia coli (STEC) are a major foodborne pathogen. Cattle are the asymptomatic reservoir of STEC with bacteria being released to the environment via their feces. STEC O157 is the main serogroup causing human illness. However, infections with non-O157 STEC are increasing: more than 70% of non-O157 infections are caused by six serogroups of non-O157, referred as "Big six" (O26, O45, O103, O111, O121, and O145). In addition, there was a large 2011 outbreak in Europe caused by STEC O104. The objectives of my thesis were: 1) To assess the prevalence of seven serogroups of non-O157 STEC (O26, O45, O103, O104, O111, O121, and O145) (STEC-7) in house flies and stable flies collected from confined cattle environments; 2) To investigate the vector competence of house flies for non-O157 STEC-7. A total of 463 house flies from feedlots and dairies from six states, and 180 stable flies collected from a feedlot in Nebraska were processed for the isolation and identification of STEC-7 using a culture-based approach followed by PCR for the confirmation of serogroups, and virulence genes. A total of 34.3% of house flies and 1.1% of stable flies tested positive for at least one serogroup of E. coli of interest, and 1.5% of house flies harbored STEC with the Shiga-toxin gene (stx1). No STEC were detected in stable flies. Vector competence bioassays for non-O157 STEC revealed that house flies can carry non-O157 STEC for at least six days with the exception STEC O145. Overall, the findings of this research demonstrate that house flies, but not stable flies, likely play an important role in the ecology and transmission of non-O157 STEC in confined cattle environments.
Keywords: House fly; Stable fly; Cattle; Shiga-toxigenic Escherichia coli; Manure; Entomology (0353)